Tech Sector Tango. - McCarthy, Ellen (Appalachian Journal)
Reports on the decision of U.S. government contractors CGI-AMS Inc. and Northrop Grumman Corp. to start building technology centers and to hire software engineers in Lebanon, Virginia in 2006. Russell County Administrator Jim Gillespie is said to have tried to help lure government contractors and they also speak of the number of software engineers that will be hired by CGI-AMS and the many reasons for the decision of the companies to build technology centers in the town.